The rise and fall of the mining industry in Zimbabwe with particular reference to Ziscosteel - Mutero, Morris (Midlands State University, 2018)
This study focuses on the rise and fall of the mining industry in Zimbabwe focusing on ZISCOSTEEL. The study was carried out in Redcliff the home town of ZISCO. This research was mainly based on primary sources which includes books, news papers, archived company files and most importantly oral interviews. It was found out that the iron and steel industry dates back to pre-colonial times were indigenous people mined and processed iron to make tools like axes, hoes and weapons. Large scale commercial iron and steel industry commenced in colonial times with the establishment of Rhodesia Iron and Steel Company (RISCO) in 1942 up until the company was confiscated by the Zimbabwean government. It was renamed Zimbabwean Iron and Steel Company in 1980. The study focuses on various expansion projects that were carried out in ZISCO and the role the company has played in the country’s economy and society. The research found out that the company started having production problems in the early 2000s and eventually stopped operations in 2008. The study highlights that several attempts were made to try and resuscitate the gigantic steel works like pre-financing, looking for private investors but all these failed. The research discovered that the collapse of ZISCO manifested rapacious socio—economic impacts on Zimbabwe.